The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0308-8146(01)00352-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical modifications of proteins: disulfide bonds reduction

Abstract: Electrochemical reduction of lysozyme disulfide bonds was achieved at pH between 10 and 11. Below pH 10, no disulfide bond cleavage was observed. At pH higher than 12, the cleavage of disulfide bonds is essentially due to hydrolysis. The addition of denaturant considerably enhanced the performance of the electrochemical device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…A similar procedure was reported previously. 23, 24 On the basis of the ESMS results, the pathway of S-S bond cleavage in GSSG is described in Scheme 1. The HPLC chromatogram of the reaction between [Pt-(Met)Cl 2 ] and GSSG showed that at least four species appeared within 24 h, but the peaks are barely identifiable except that of GSSG (retention time of 1.35 min).…”
Section: Discussionmentioning
confidence: 99%
“…A similar procedure was reported previously. 23, 24 On the basis of the ESMS results, the pathway of S-S bond cleavage in GSSG is described in Scheme 1. The HPLC chromatogram of the reaction between [Pt-(Met)Cl 2 ] and GSSG showed that at least four species appeared within 24 h, but the peaks are barely identifiable except that of GSSG (retention time of 1.35 min).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that the effect of increasing voltage during the superimposition of an electrical field upon cross-flow membrane filtration of a complex peptide mixture results not only in a higher fractionation due to the higher electrical field applied but also in a higher chemical modification of the peptides. This leads to a lower concentration of the original peptides, which is in accordance to Cayot et al (1999Cayot et al ( , 2002 and Hawkins et al (2003).…”
Section: Determination Of Lactose Modification Via Hplcmentioning
confidence: 54%
“…As a result, molecular water splitting is processing faster due to the ions, which again carry electrical voltage. In the case of solutions containing proteins, peptides, or amino acids, this effect may also influence the chemical modification of molecules to be fractionated by an electrical field (Bazinet et al 1997a, b;Cayot et al 1999Cayot et al , 2002. In detail, hypochlorite-induced oxidation of peptides depends on the amino acid sequence of these peptides and their reactive side chains.…”
Section: Introductionmentioning
confidence: 99%
“…We can expect to exploit the protolytic effect of the oxidized thiols due to possibility of cleavage of the disulfide bond -S-Son the MMCFE surface with its subsequent eventual protonation [38]. The oxidised thiols studies, HCySS and GSSG, have more accentuated differences in comparison with the similarities registered for the reduced thiols.…”
Section: Cyclic Voltammetry Of Oxidized Thiolsmentioning
confidence: 99%